1977
DOI: 10.1128/jb.129.1.138-144.1977
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and preliminary characterization of auxotrophic and morphological mutants of the yeastlike form of Paracoccidioides brasiliensis

Abstract: N-methyl-N'-nitro-N-nitrosoguanidine, which is known to be a very effective mutagen in many systems, was used to induce mutants in the yeastlike form of Paracoccidioides brasiliensis strain IVIC Pb9, an imperfect fungus. Forty-three auxotrophic and 27 prototrophic morphological mutants were isolated after treatment with 50 ug of nitrosoguanidine per ml in 0.1 M citrate buffer, pH 5.0. Auxotrophic mutants required primarily either amino acids, purines, or pyrimidines. Some auxotrophs were also morphological mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Accordingly, studies on the nutritional requirements of this dimorphic pathogen revealed that different levels of thiamine auxotrophy were widespread among a collection of 25 H. capsulatum isolates with some isolates deriving from human infections ( Mcveigh and Morton, 1965 ). Thiamine auxotrophy has also been described for several Paracoccidioides brasiliensis isolates ( San Blas and Centeno, 1977 ) which is the major cause of Paracoccidiomycosis in Latin America ( Ferreira, 2009 ). This shows that thiamine requirement is frequently observed in pathogenic yeasts and dimorphic fungi but has not been described for wild-type isolates of a saprophytic and generally free-living filamentous fungus.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, studies on the nutritional requirements of this dimorphic pathogen revealed that different levels of thiamine auxotrophy were widespread among a collection of 25 H. capsulatum isolates with some isolates deriving from human infections ( Mcveigh and Morton, 1965 ). Thiamine auxotrophy has also been described for several Paracoccidioides brasiliensis isolates ( San Blas and Centeno, 1977 ) which is the major cause of Paracoccidiomycosis in Latin America ( Ferreira, 2009 ). This shows that thiamine requirement is frequently observed in pathogenic yeasts and dimorphic fungi but has not been described for wild-type isolates of a saprophytic and generally free-living filamentous fungus.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of dimorphism is observed in some human pathogenic fungi, among them Paracoccidioides brasiliensis. Until recently, the transition from the mycelial (M) to the yeast-like (Y) phase in this micro-organism was considered to be essentially heat dependent [ 17,181. More recent reports have suggested that nutritional factors, among others, may be also involved in the regulation of dimorphism in P. brasiliensis [ 1 1, 14, 19, 201, although the mechanisms of morphological transition have not been fully clarified [3, 111. Profound transformations in the polysaccharide composition of the cell wall accompany the transition between the mycelial and yeast-like phase: j3-1,3-glucans predominate in the former, whereas a-1,3-glucans are only observed in the latter [21].…”
Section: Discussionmentioning
confidence: 99%